Effect of Feeding Synbiotic on Growth and Health Performance of Jersey Crossbred Calves - Sahu, Jyotimala; Rai, Saroj; Behera, R.; Mandal, D. K.; Ghosh, M. K.; Mondal, M. (International Journal of Livestock Research, 2019)
An experiment was conducted to study the effect of synbiotic formula (Lactobacillus rhamnosus NCDC 298 + Fructo-oligosaccharide) on growth (dry matter intake, body weight and body measurements) and health performance (disease incidences, faecal score and parasite oocyst count) of Jersey crossbred calves. The bacterial load was enumerated during the synbiotic feeding period of 42 days and post feeding up to 90 days of age. Study was carried out in Jersey crossbred calves maintained at NDRI-ERS, Kalyani from September 2017 to January 2018. The calves in the treatment group were fed 100 ml synbiotic having a bacterial load of 109 CFU/ml while control group were maintained in existing routine practices. There was significant improvement in final body weight (kg, P<0.01), average daily gain (g, P<0.05) and fecal score (P<0.05) in the synbiotic fed group. No trend was observed on the internal parasites even after feeding synbiotics. Therefore, it may conclude that feeding synbiotic to the calves had improved effect on the body weight gain with reduced diarrhoeal incidence during the study period.